Empoderamiento de la mujer y habilidades gerenciales en el hospital básico base aérea Cotopaxi (BACO). - Pastuña Ante, Diana Johana (2023)
This research project focused on the empowerment of women and managerial skills, which are variables named with values, strengths, competencies and social support system, part of its attractive concept that comes from its emphasis on positive aspects of the behavior of the human being. human, identify and foster skills and promote well-being, rather than curing problems or identifying risk factors. The objective is to determine how managerial skills influence the empowerment of women in the Cotopaxi Air Base Basic Hospital, for which the concepts and theoretical bases of women's empowerment and managerial skills were investigated, the empowerment factors were diagnosed and managerial skills that predominate in the company to propose strategies based on the results obtained in the diagnosis that allow women to empower themselves in each position. Considering the objectives of this study, the research was determined through a quantitative approach since data from the survey was collected and analyzed and the hypothesis was not verified, whose value is not acceptable for case studies; the value obtained from the Cronbach's Alpha Coefficient in the empowerment variable is 0.546% and a Cronbach's alpha coefficient equal to 0.638 in the managerial skills variable, through the application of the questions it was possible to show that the percentage of participation of women in The Cotopaxi Air Base Basic Hospital is becoming more important since previously it was known that there were only two women working for a period of no more than 12 years, a situation that has now been overcome since in the last year they have joined the work team a total of 7 women, equivalent to 0.26% of the total number of working women, which added to the women who have been in the institution for 4 years, adds up to 0.50% of the total number of women who work at the Cotopaxi Air Base Basic Hospital, opening the possibility that women assume positions of power and leadership in the short and medium term.